The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.4049/jimmunol.175.2.884
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Follicular Dendritic Cell Networks by Activated T Cells: The Role of CD137 Signaling

Abstract: B cells, but not T cells, are considered to be important for the formation of follicular dendritic cell (FDC) clusters. Stimulation with agonist mAbs against CD137 (4-1BB), a TNFR family member primarily expressed on activated T cells, was effective in promoting T cell responses, but paradoxically suppressed T-dependent humoral immunity and autoantibody production in autoimmune disease models. Our present study shows that agonistic anti-CD137 treatment activates T cells, resulting in diminished FDC networks in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 38 publications
(44 reference statements)
5
23
0
1
Order By: Relevance
“…B cell loss was not seen in the NZB × NZW F1 strain, but, germinal center (GC) formation, which is central to the development of functional classswitched B cells, was abolished. In accordance with the latter, a recent report also showed that anti-4-1BB inhibited GC formation apparently by diminishing follicular dendritic cell (FDC) networks in B cell follicles [62]. Whether this activity was direct or indirect via another cell type is not clear, but it is possible that again suppression of B cell immunity was accompanied by enhanced CD8 responses.…”
Section: Cd8+ Treg and Novel Immune Regulation From 4-1bbmentioning
confidence: 60%
“…B cell loss was not seen in the NZB × NZW F1 strain, but, germinal center (GC) formation, which is central to the development of functional classswitched B cells, was abolished. In accordance with the latter, a recent report also showed that anti-4-1BB inhibited GC formation apparently by diminishing follicular dendritic cell (FDC) networks in B cell follicles [62]. Whether this activity was direct or indirect via another cell type is not clear, but it is possible that again suppression of B cell immunity was accompanied by enhanced CD8 responses.…”
Section: Cd8+ Treg and Novel Immune Regulation From 4-1bbmentioning
confidence: 60%
“…Indeed, in contrast to OX40L, CD70-driven costimulation resulted in down-regulation of GCs and Ab responses. 4-1BBL promoted infiltration of B cell follicles by CD4 and CD8 T cells as well, and this also triggered inhibition of T cell-dependent humoral responses (59,60). In contrast to CD70, 4-1BBL down-regulated Ab production through CD4 and CD8 T cell-mediated destruction of follicular dendritic cell networks in B cell follicles rather than through a GC B celldependent pathway (60).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that agonist Abs to 4-1BB can be highly suppressive for humoral responses (28,29) and for a number of autoimmune responses (30 -34). Also, other data have now shown enhanced responses in 4-1BB-deficient animals (35,36).…”
Section: Functional Dichotomy Between Ox40 and 4-1bb Inmentioning
confidence: 99%